Produktivitas Drilling Rig pada Pekerjaan Pondasi Bore Pile Proyek Pembangunan RS Muhammadiyah Gresik - Ardiyanti, Nadila (Jurnal Vokasi Teknik Sipil, 2023)
Productivity and budget are the keys to determining the efficiency and success of carrying out bore pile foundation work. This research method involves collecting data on productivity and budgeting costs for heavy drilling equipment. This research includes the productivity of bore pile foundation drilling, the time needed to complete the work, and the budget required for operating heavy equipment during implementation. Factors that affect productivity are also analyzed, this aims to determine the strategy used to increase productivity. This research method is descriptive quantitative. The results showed that use of a Kobelco BM 500 type drilling rig with a CMV drilling machine had a productivity of 9.88 m/hour with a drilling diameter of 60cm. The realization time is 38 days, and the effective time is 30 days. The budgeted costs incurred amounted to IDR 268,742,070. Factors that affect the productivity level of drilling rigs include: land conditions, weather factors, equipment maintenance and repair, refueling and lubricating oil, drilling diameter and depth, and the use of several heavy pieces of equipment simultaneously.